Effects of Resistance Training Volume on MMPs in Circulation, Muscle and Adipose Tissue - de Sousa Neto, Ivo Vieira; Tibana, Ramires Alsamir; da Cunha Nascimento, Dahan; Vieira, Denis César Leite; Durigan, Joao Luiz Quagliotti; Pereira, Guilherme Borges; Navalta, James Wilfred; de Cássia Marqueti, Rita; Prestes, Jonato (International Journal of Sports Medicine, 2017)
The aim of this study was to investigate the effects of different resistance training (RT) volumes on MMP activity in skeletal muscle, visceral adipose tissue and circulation. 21 Wistar rats were randomly divided into 3 groups (n=7 per group): sedentary control (SC); RT with 4 ladder climbs (RT-4; 50, 75, 90 and 100% of their maximal carrying capacity) and RT with 8 ladder climbs (RT-8 with 2 sets for each load). The 8-week RT consisted of climbing a 1.1-m vertical ladder with weights secured to the animals’ tails. MMP-2 and -9 activity were analyzed by zymography. RT-8 displayed higher active MMP-2 activity as compared with SC and RT-4 in skeletal muscle (p<0.05). There was no significant difference between groups for pro and intermediate-MMP-2 activity in visceral adipose tissue, while RT-8 presented lower active MMP-2 activity as compared with SC (p<0.05). Plasma pro and active MMP-2 and MMP-9 activity was lower in RT-8 as compared with RT-4 (p<0.05). These results suggest that higher volume RT up-regulates MMP-2 activity in skeletal muscle, while down-regulating MMP-2 in visceral adipose tissue. Moreover, it induces a decrease of MMP-2, 9 activity in circulation. Different tissue and circulatory MMP responses to RT may result in specific remodeling.
Keywords: tissue remodeling; exercise training; matrix metallopeptidase; training volume